Haptoglobin Hp2 Variant Promotes Premature Cardiovascular Death in Stroke Survivors. Issue 6 (June 2017) - Ijäs, Petra; Melkas, Susanna; Saksi, Jani; Jula, Antti; Jauhiainen, Matti; Oksala, Niku; Pohjasvaara, Tarja; Kaste, Markku; Karhunen, Pekka J.; Lindsberg, Perttu; Erkinjuntti, Timo
Abstract : Background and Purpose—: Haptoglobin (Hp) is an acute phase plasma protein protecting tissues from oxidative damage. It exists in 2 variant alleles ( hp1/hp2 ) giving rise to 3 protein isoforms with different biochemical properties and efficiency to limit oxidative stress. We previously found that hp2 variant is associated with stroke risk in the patients with carotid stenosis and the risk of ischemic cardiovascular events in a general population cohort. This study examined the hypothesis that Hp genotype is associated with general cardiovascular risk in patients with stroke. Methods—: Hp was genotyped in SAM study (Helsinki Stroke Aging Memory, n=378). A total of 1426 individuals ascertained from a nationally representative cross-sectional health survey served as population controls. Results—: Hp genotype frequencies were 15.6% ( hp1-1 ), 44.2% ( hp1-2 ), and 40.2% ( hp2-2 ) in patients with stroke. During a mean of 7.5-year follow-up after first-ever stroke, hp2 carriers had a substantially higher rate of cardiac deaths (24.5% versus 8.5%; P =0.006) and a trend toward more fatal strokes (23.5% versus 13.6%; P =0.122). The combined risk of ischemic cardiovascular deaths was 2.4-fold higher among hp2 carriers (95% confidence interval, 1.28–4.43) after adjustment for major cardiovascular risk factors. Conclusions—: Hp2 allele is associated with premature ischemic cardiovascular deaths after first-ever ischemic stroke. Abstract : Supplemental Digital Content is available in the text.